The Productivity Effect of Non-Union Representation - Steffen Mueller (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2009)
Declining union density in many industrialized countries directs attention to alter- native ways of labor relations and worker representation as, e.g., works councils. German works councils belong to the most powerful worker representations in de- veloped countries but little is known of their causal effect on productivity. A large linked employer-employee panel is used to examine this issue. Comparing firms with and without a works council I find that firms with a works council are on average 6.5 percent more productive. I present evidence that this estimate is the lower bound to the causal productivity effect of works councils.
Keywords: D24; J53; 330; worker participation; works council; productivity